2008
DOI: 10.1007/s11999-007-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is a Saline Arthrogram for Wounds Around the Knee?

Abstract: Traumatic arthrotomies may predispose patients to subsequent septic arthritis and therefore are regarded as serious injuries requiring emergent treatment. The saline arthrogram is a commonly used test to determine if a patient has a traumatic arthrotomy. We determined the sensitivity of the saline arthrogram to identify known intraarticular wounds in 78 patients (80 knees) undergoing elective arthroscopic procedures. There were 66 infrapatellar and 14 suprapatellar incisions. The average length of the incision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
0
20
1
Order By: Relevance
“…The observed wide range of the knee volume (40-290 ml) explains the low sensitivity and specificity of the saline load test that is used to determine a traumatic capsule defect [9][10][11][12]. This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed wide range of the knee volume (40-290 ml) explains the low sensitivity and specificity of the saline load test that is used to determine a traumatic capsule defect [9][10][11][12]. This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate in these studies is between 36% and 46% at clinically accepted volumes of 50 to 60 mL. [4][5][6] Our rate was only 33% at 180 mL, whereas other studies had an improved sensitivity in the 90% to 99% range at this volume. Nord et al used a dynamic test by putting the knee through a range of motion during injection, which may have accounted for their improved sensitivity at higher volumes (99% at 175 mL).…”
Section: Discussionmentioning
confidence: 64%
“…5 However, Tornetta et al still found very low sensitivity even when the dynamic test was used. 6 The static test was chosen for this study because the dynamic test was felt to introduce too many confounding variables, including cycling rate and range of motion in degrees. Also, the static test may be more clinically relevant in an awake patient who may not tolerate range of motion on a painful, injured knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation